Manajemen Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru Pendidikan Agama Islam - Husni Tamrin; Nuzuar Nuzuar; Syahrial Dedi (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this study was to determine the management of madrasa principals in improving the professional competence of Islamic religious education teachers. In this study, the authors used a type of qualitative research with a descriptive approach that is research that describes or illustrates the state or status of phenomena. The results of the study, several things that need to be done by the madrasa head include: 1) Knowing the condition / condition of the teacher in the background of environmental, social and economic life, 2) stimulating the teacher's work spirit in various ways, 3) maintaining the availability of facilities needed to develop the ability teacher, 4) increasing teacher participation in the school environment, 5) fostering a sense of family within the school environment, 6) strengthening the relationship of the school with the community, committee and student guardians. Conclusions, the management of madrasas in improving the professional competence of Islamic religious education teachers (PAI) are: 1) involving teachers in training activities, 2) promoting discipline, 3) motivating teachers, 4) supervision. Conclusion, The application of the management of the madrasa head at the MA Al-Manshuriyah Sungai Baung has already been implemented, the professional competence of PAI teachers at the Al-Manshuriyah MA has been very good Keywords: Principal Management, PAI Teacher Competence